Genetic and Agronomic Analysis of Tobacco Genotypes Exhibiting Reduced Nicotine Accumulation Due to Induced Mutations in Berberine Bridge Like (BBL) Genes - Lewis, Ramsey S.; Drake-Stowe, Katherine E.; Heim, Crystal; Steede, Tyler; Smith, William; Dewey, Ralph E. (Frontiers in Plant Science, 2020)
Genetic methodologies for reducing nicotine accumulation in the tobacco plant (Nicotiana tabacum L.) are of interest because of potential future regulations that could mandate lowering of this alkaloid in conventional cigarettes. Inactivation of tobacco genes such as the Berberine Bridge Like (BBL) gene family believed to encode for enzymes involved in one of the latter steps of nicotine biosynthesis could be a viable strategy for producing new tobacco cultivars with ultra-low leaf nicotine accumulation. We introduced deleterious mutations generated via ethyl methanesulfonate treatment of seed or gene editing into six known members of the BBL gene family and assembled them in different combinations to assess their relative contribution to nicotine accumulation. Significant reductions (up to 17-fold) in percent leaf nicotine were observed in genotypes homozygous for combined mutations in BBL-a, BBL-b, and BBL-c. The addition of mutations in BBL-d1, BBL-d2, and BBL-e had no additional significant effect on lowering of nicotine levels in the genetic background studied. Reduced nicotine levels were associated with reductions in cured leaf yields (up to 29 %) and cured leaf quality (up to 15 %), evidence of physiological complexities within the tobacco plant related to the nicotine biosynthetic pathway. Further nicotine reductions were observed for a BBL mutant line cultivated under a modified production regime in which apical inflorescences were not removed, but at the expense of further yield reductions. Plants in which BBL mutations were combined with naturally occurring recessive alleles at the Nic1 and Nic2 loci exhibited further reductions in percent nicotine, but no plant produced immeasurable levels of this alkaloid. Findings may suggest the existence of a minor, alternative pathway for nicotine biosynthesis in N. tabacum. The described genetic materials may be of value for the manufacture of cigarettes with reduced nicotine levels and for future studies to better understand the molecular biology of alkaloid accumulation in tobacco.